Writing connections you, college, and careers. : sentences and paragraphs - Brandon, Lee E. (Houghton Mifflin, 2004)
Designed specifically for community colleges and business programs, Writing Connections helps students of varying backgrounds, ages, and majors recognize how strong writing skills can allow them to achieve both their academic and professional goals. Students practice finding common denominators and patterns across all key forms of writing and learn to apply what they learn to personal, cross-curricular, and workplace writing. Student examples illustrate all stages of the writing process and serve as good models on which students can pattern their own work.